Cephalexin Induced Cholestatic Jaundice - Abhinav Agrawal; Mana Rao; Sarfaraz Jasdanwala; Ajay Mathur; Margaret Eng (Case Reports in Gastrointestinal Medicine)
Cephalexin is a very commonly prescribed orally administered antibiotic which has many potential side effects. Amongst these cholestatic jaundice has been infrequently reported as an adverse reaction. We present a case of a 57-year-old male who exhibited features of cholestatic jaundice including elevated liver function tests (LFTs) after taking cephalexin and showed improvement on removal of the offending agent. During this time he was symptomatically treated with cholestyramine. Complete resolution of LFTs was seen in four weeks. Cephalexin induced cholestasis is rare and hence requires a high degree of clinical suspicion for prompt diagnosis and treatment.